A 3D human liver model of nonalcoholic steatohepatitis - Duriez, Marion; Jacquet, Agnes; Hoet, Lucile; Roche, Sandrine; Bock, Marie-Dominique; Rocher, Corinne; Haussy, Gilles; Vigé, Xavier; Bocskei, Zsolt; Slavnic, Tamara; Martin, Valérie; Guillemot, Jean-Claude; et al. (Journal of clinical and translational hepatology, 2020)
Background and Aims: To better understand nonalcoholic steatohepatitis (NASH) disease progression and to evaluate drug targets and compound activity, we undertook the development of an in vitro 3D model to mimic liver architecture and the NASH environment.
Gesehen am 31.03.2025